Histopathological Spectrum of Premalignant and Malignant Lesions of Esophagus in the Population of Karachi - Asma Shabbir; Muhammad Asif Qureshi; Nehad Khan; Talat Mirza (ziauddin University, 2020)
Background: Squamous cell carcinoma (SCC) and adenocarcinoma are the most common esophageal cancers. Barrett's esophagus is the change of esophageal stratified squamous epithelium to columnar cells which if remain undiagnosed follows the dysplasia - carcinoma sequence. The last two decades show a change in the histologic pattern of esophageal carcinoma. Adenocarcinoma is at majority rate than SCC in the West, however, in Asia, SCC is still the commonest cancer of esophagus. In this study, we aim to define a spectrum of premalignant and malignant neoplasms of esophagus in our region. Methods: This study was done at Dow Diagnostic Research and Reference Laboratory (DDRRL). All the cases of preneoplastic and neoplastic lesions of esophagus received during the period of 7 years (2009-2015) were reviewed. The data obtained were subjected to descriptive statistical analysis using SPSS version 21. Results: Out of 94 premalignant cases, 70 (74.5%) were diagnosed as Barrett's esophagus, 23 (24.5%) as dysplasia and 1 (1.1%) as adenoma. From the total of 450 malignant cases, 395 (87.7%) were SCC, 54 (12%) were adenocarcinoma and a single case of leiomyoma was diagnosed. Grade II SCC was found to be most the common lesion. Conclusion: Barrett's esophagus was more than dysplasia and showed male preponderance. SCC was the predominant esophageal cancer, which is similar to the other studies in our country. SCC was found more common in females than males and vice versa for adenocarcinoma. Majority of all the cases belonged to 41-60 years of age group.